Analisis Miskonsepsi Matematis: Dampak Strategi Pembelajaran Predict Discuss Explain Observe Discuss Explain - Ernawati, Ernawati; andriani, Siska; Farida, Farida; Sri Anggoro, Bambang (Desimal: Jurnal Matematika, 2019)
This study aims to determine the effect of PDEODE learning strategies on students' misconceptions. This research is a quantitative research type Quasi Design Experiment using PDEODE learning strategies there are 6 stages in this learning namely 1) Predict 2) Discuss 3) Explain 4) Observe 5) Discuss 6) Explain. The population in this study were all students of class VIII at MTs Al-Hikmah Kedaton Bandar Lampung in the 2019/2020 school year. The sample in this study was class VIII D (Control Class using conventional methods) and VIII E (Experiment Class using the PDEODE learning strategy). Data collection instruments used were RPP, multiple choice test instruments accompanied by a scale of confidence given to material experts and question experts to determine the feasibility of the learning instrument and given to students (Pretest and Posttest). Based on the results of mathematics learning research using the PDEODE strategy for students' misconceptions is more effective than mathematics learning using conventional methods.